2011
DOI: 10.5535/arm.2011.35.5.733
|View full text |Cite
|
Sign up to set email alerts
|

Dural Arteriovenous Fistula on the Brain Stem and Upper Cervical Spinal Cord - A Case Report -

Abstract: A 53-year-old man abruptly developed headache and unconsciousness. Brain computed tomography (CT) and CT angiography showed subarachnoid hemorrhage, intraventricular hemorrhage, and multiple tortuous vascular structures on the brain stem and upper cervical spinal cord. Four-vessel angiography displayed intradural ventral arteriovenous fistula, supplied by the left vertebral and occipital arteries. Drainage was via both sigmoid sinus and cervical venous plexus. He had been treated with transarterial coil emboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Treatment options for SDAVF include endovascular embolization and surgical ligation of the stula [28][29][30][31][32][33][34][35][36][37][38] . Endovascular embolization is less invasive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment options for SDAVF include endovascular embolization and surgical ligation of the stula [28][29][30][31][32][33][34][35][36][37][38] . Endovascular embolization is less invasive.…”
Section: Discussionmentioning
confidence: 99%
“…5 cases of them had sensory dysfunction or numbness, 1 28 30 37 38 6 cases of them had decreased strength or even gait instability, 30-32, 37, 38 1 cases had hemiplegia 31 and 1 case had quadriplegia, 33 However, the mild complications of the cases recovered quickly, only 3 more serious cases received rehabilitation treatment. 31,35,37 At present, the effect of extracorporeal shock waves on spasticity caused by central diseases is not clear. 18 We used extracorporeal shock waves to treat lower limb motor dysfunction caused by spasticity in hemiplegic patients and found that extracorporeal shock waves can effectively reduce spasticity caused by central system disorders.…”
Section: Discussionmentioning
confidence: 99%
“…For a successful and safe endovascular embolization of D-AVF fed by the APA, detailed inspection of superselective angiogram and precise recognition of anatomical configuration are mandatory, because the APA is notorious for dangerous anastomoses to the carotid and vertebral arteries as well as vital supply to the cranial nerves 9, 10, 11, and 12 via the neuromeningeal trunk. 1) 6) 8) 10) 19) 21) Although embolization of D-AVF using polyvinyl alcohol particles, isobutyl 2-cyanoacrylate, and n-butyl cyanoacrylate has been previously described, it is well known that these materials are often related with incomplete occlusion and recanalization after the treatment due to the poor distal penetration and inadequate delivery of the embolisates. 24) Recently, Onyx has been increasingly used to treat such lesions because it enables prolonged and controlled injection with enhanced penetration to the target.…”
Section: Discussionmentioning
confidence: 99%